Cause of Subdural Hemorrhage in Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The frequency of child abuse and unintentional injury as a cause of infant and toddler subdural hedmorrhage (SDH) was determined by a prospective study of 66 cases admitted to Harborview Medical Center, a level I pediatric trauma center, and the Children's Hospital and Regional Medical Tertiary Care Center, Seattle, WA, from March 1995 through December 1998.